PENDAMPINGAN HYGIENE DAN SANITASI PRODUKSI JAJAN ULI DAN BEGINA KELOMPOK PKK SRATI BANTEN BEDULU GIANYAR - Ni Kadek Dwipayani Lestari; I Gusti Ayu Ika Monika Prastyandhari; Gerson Feoh; Ni Putu Widiastuti (Universitas Mataram, 2026)
In Bedulu Village, precisely in Banjar Margasengkala, there are very strong customs for religious ceremonies, because there is a Griya, where the Dewa Yadnya ceremony is held. This makes the area potential to develop cultural-based products, namely ceremonial snacks carried out by the Srati Banten group consisting of local PKK mothers to work on various facilities and ceremonial snacks. The Srati Banten group has problems in hygiene and sanitation of production, financial and production management and online marketing. Activities are carried out through 5 stages of service, namely socialization, technology delivery to partners, hygiene and production training, training in making 2 types of ceremonial snacks, packaging training, financial management and production management assistance and online marketing assistance. The results of the service are an increase in the average knowledge of Srati Banten group partners in all activities by 25%.. Increased shelf life of ceremonial snacks from 3 days to 14 days. Partners have more hygienic products, more attractive and competitive packaging.